Penetapan Kadar Asetosal dengan Metode Asidi-Alkalimetri - Rifani Hutami Supardi; Sekar Ayu Pratiwi; Iman Iswanto; Agnes Verensia Merentek; Amanda Upara; Satria Tidore; Nesa Sari Penga (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The determination of the active pharmaceutical ingredient is an essential step in pharmaceutical quality control to ensure the safety, efficacy, and compliance of drug products with the standards established by the Indonesian Pharmacopoeia. One of the analytical methods commonly used to determine the content of acetylsalicylic acid (aspirin) is the acid-alkalimetric method using back titration. This experiment aimed to determine the acetylsalicylic acid content in aspirin tablets using the acid-alkalimetric method and to evaluate its compliance with the requirements of the Indonesian Pharmacopoeia, Sixth Edition. The analysis was carried out by reacting a 60 mg aspirin sample with an excess of 0.1 N sodium hydroxide (NaOH), followed by back titration of the excess base with standardized 0.1 N hydrochloric acid (HCl) using phenolphthalein as the indicator. The experimental results showed that the HCl volume required for the blank solution was 15.8 mL, while the sample required 7.0 mL. The calculated acetylsalicylic acid content was 158.54 mg, corresponding to 379.43 mg per tablet or 379.4% of the labeled claim. This result exceeded the acceptable range specified in the Indonesian Pharmacopoeia, Sixth Edition, which requires the active ingredient content to be between 90.0% and 110.0% of the labeled amount. The discrepancy was likely caused by experimental errors, including inaccurate burette readings, improper endpoint determination, errors in solution standardization, or calculation mistakes. Therefore, careful execution of each analytical step is essential to obtain accurate and reliable assay results.